Trivialization of Aggression Against Women in India: An Exploration of Life Writings and Societal Perception - Arya, S.; George, Allen Joshua (Frontiers in Psychology, 2022)
Purpose Aggression, or an action that intend to harm, encompasses different forms with varying intensity, impact, and salient features. Globally and in Indian context specifically, aggression against women is often normalized if there is no physical aggression involved as the hurt caused tends to be invisible. The current study explored the perceived intensity of physical, verbal, and sexual aggression among south Indian adults. Method Aggressive instances from the life writings of two south Indian women were chosen and were rated by five independent coders to check inter-coder reliability. The select narratives disclose instances of domestic aggression. Ten instances with highest ratings were chosen as the material for data collection. Adults (N = 145) from two southern states had reported the perceived intensity of aggression in each context. Textual analysis and ANOVA were the analytic techniques adopted. Results The results indicate trivialization of verbal aggression compared to physical and sexual aggression. Further, the instances of verbal or more subtle aggression were perceived as even more trivial when the respondents got exposed to the instances of explicit physical and sexual aggressions first. Conclusions The findings indicate trivialization of verbal and implicit forms of aggression, particularly when exposed along with physical and explicit forms of aggression. Consequences of different forms of aggression were not considered significant by the respondents. Suggestions for further studies, changes in policy-making, and law-enforcement were made based on the current results.